A Mediterranean-like dietary pattern with vitamin D3 (10 µg/d) supplements reduced the rate of bone loss in older Europeans with osteoporosis at baseline: results of a 1-y randomized controlled trial. Issue 3 (11th July 2018) - Jennings, Amy; Cashman, Kevin D; Gillings, Rachel; Cassidy, Aedin; Tang, Jonathan; Fraser, William; Dowling, Kirsten G; Hull, George L J; Berendsen, Agnes A M; de Groot, Lisette C P G M; Pietruszka, Barbara; Wierzbicka, Elzbieta; et al.
ABSTRACT: Background: The Mediterranean diet (MD) is widely recommended for the prevention of chronic disease, but evidence for a beneficial effect on bone health is lacking. Objective: The aim of this study was to examine the effect of a Mediterranean-like dietary pattern [NU-AGE (New Dietary Strategies Addressing the Specific Needs of the Elderly Population for Healthy Aging in Europe)] on indexes of inflammation with a number of secondary endpoints, including bone mineral density (BMD) and biomarkers of bone and collagen degradation in a 1-y multicenter randomized controlled trial (RCT; NU-AGE) in elderly Europeans. Design: An RCT was undertaken across 5 European centers. Subjects in the intervention group consumed the NU-AGE diet for 1 y by receiving individually tailored dietary advice, coupled with supplies of foods including whole-grain pasta, olive oil, and a vitamin D3 supplement (10 µg/d). Participants in the control group were provided with leaflets on healthy eating available in their country. Results: A total of 1294 participants (mean ± SD age: 70.9 ±4.0 y; 44% male) were recruited to the study and 1142 completed the 1-y trial. The Mediterranean-like dietary pattern had no effect on BMD (site-specific or whole-body); the inclusion of compliance to the intervention in the statistical model did not change the findings. There was also no effect of the intervention on the urinary biomarkers free pyridinoline or free deoxypyridinoline. Serum 25-hydroxyvitamin D significantly increased and parathyroid hormone decreased ( P  < 0.001) in the MD compared with the control group. Subgroup analysis of individuals with osteoporosis at baseline (site-specific BMD T-score ≤ −2.5 SDs) showed that the MD attenuated the expected decline in femoral neck BMD ( n  = 24 and 30 in MD and control groups, respectively; P  = 0.04) but had no effect on lumbar spine or whole-body BMD. Conclusions: A 1-y intervention of the Mediterranean-like diet together with vitamin D3 supplements (10 µg/d) had no effect on BMD in the normal age-related range, but it significantly reduced the rate of loss of bone at the femoral neck in individuals with osteoporosis. The NU-AGE trial is registered at clinicaltrials.gov as NCT01754012.